James D. G. Dunn, “The Oral Gospel Tradition”, Grand Rapids, MI / Cambridge: Eerdmans, 2013. - ZAMFIR, Korinna (Studia Universitatis Babeș-Bolyai Theologia Catholica Latina, 2015)
James Dunn’s collected essays on the oral traditions behind the canonical gospels call attention to the importance of the oral transmission of logia and narratives in the ancient culture that produced the gospels, in a world where the degree of literacy was fairly low. The essays also recap Dunn’s earlier work on memory. The volume brings together four decades of scholarship.